Discovery and significance of tempestites and storm deposits in the Qingshankou Formation of the Gulong Sag, northeastern China - He, Wenyuan; Zhong, Jianhua; Sun, Ningliang (Frontiers in Earth Science, 2023)
The Qingshankou Formation in the Gulong Sag has attracted significant attention due to its rich shale oil reserves. However, several fundamental geological problems associated with shale from the Qingshankou Formation remain unresolved. The Qingshankou Formation in the Gulong Sag is a set of deep-lake and semi-deep-lake fine-grained deposits primarily composed of mudstone and shale. Recent studies have shown that tempestites and storm deposits commonly occur in the Qingshankou Formation. Fine liquefaction veins often occur at the bottom of the tempestite, indicating that storm-shaking liquefaction is expected in the swale structure. Meanwhile, the mudstone and shales primarily have a sand structure with fine grain size, indicating that the environment is exposed to an undercurrent activity, with a water flow velocity of 20–55 cm s−1. Unlike previous studies, we posit that the ancient water depth was only 20–30 m or shallower. These phenomena have significance for understanding the formation environment and diagenetic process of shale in the first member of the Qingshankou Formation, which provides a reference for oil and gas exploration and development.